Influence of information published on Instagram about exclusive breastfeeding on first-time mothers in the Colombian League of La Leche - Luna-Granados, Nidia Yazmin; Rojas-Luna, Leidy Rocio; Portilla-Portilla, Edwin Mauricio (Universidad y Salud, 2026)
Introduction: Information posted on Instagram about exclusive breastfeeding has influenced the knowledge and practices of first-time mothers. Objective: To analyze the influence of exclusive breastfeeding information published on Instagram on first-time mothers in the city of Pamplona, Colombia. Materials and Methods: A mixed-methods study was conducted. In the quantitative phase, a Likert-scale survey was applied to 57 first-time mothers who were members of the Liga de la Leche Colombia, in order to characterize the population and establish inclusion criteria. In the qualitative phase, a focus group was conducted with 8 of these mothers, selected according to the established criteria, to explore in depth their perceptions and experiences regarding exclusive breastfeeding information published on Instagram. Qualitative data were analyzed using Atlas.ti7 software and grounded theory methodology with open, axial, and selective coding. Results: Thirty-four codes were identified, highlighting the benefits of breastfeeding, strategies for verifying information on Instagram, and changes in exclusive breastfeeding practices after consulting this social network. Conclusions: Instagram has become a relevant source of information for first-time mothers, significantly influencing their exclusive breastfeeding practices.